(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of anemia among children presenting with breath holding spells. Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the Pediatrics Department, Postgraduate Medical Institute, Hayatabad Medical Complex Peshawar from March 2015-August 2015. Materials and Methods: All children meeting the inclusion criteria and presenting with Breath-holding spells(BHS) were included in the study. All information was recorded in a pre-designed proforma and strictly exclusion criteria was followed to control confounders and bias in the study results. Data was stored and analyzed in SPSS version 20. Anemia was stratified among age and gender to see the effect modifications. Post stratification was done through chi-square test keeping p-value ≤ 0.05 was taken significant. All results were presented in the form of table and graphs. Results: The mean age group of our sample was 2.6 + 1.4 years of which 63.5% were male and 36.5% were female children. The mean hemoglobin concentration was 8.6 + 1.9 gm/dl of blood and 39.9% of children were confirmed to have anemia. Conclusion: There is a high incidence of anemia associated with breath holding spells. A full blood count and where possible serum ferritin level would therefore be warranted in the work up of children presenting with breath holding spells.